Aplicação de interferômetro de Sagnac para detecção de perturbações mecânicas e localização - Gaglioti, Sílvio Ferreira (2014)
Optical fibers can be applied as sensors for pressure, rotation, movement, temperature, electric flow, strength, stress, and so on. It can also be used as a transmission medium for the detected signal up to the acquisition system and data processing module. This technological solution known as “fiber optical sensors” is becoming more attractive even in applications considered impossible few years ago. Among the industry segments that take advantage of such new solutions are petroleum, electricity, telecommunications and the construction area. There are specific applications for intrusion detection in security systems that benefit from interferometry. In this case, Michelson or Sagnac interferometers are extensively explored. Such solutions can be enhanced for leakage detection systems in oil pipes, as already reported. However, when huge areas require the monitoring systems, acoustic signals or mechanical disturbances detection is not sufficient to sense intrusion or localization. The Sagnac interferometer features fits better in such systems, since its response also depends on the distance where the mechanical disturbance is applied. In this scenario, this work explores the application of the Sagnac interferometer for mechanical disturbances detections and localization around well-defined perimeters. The experimental results are compared with simulation results obtained after implementing a reported modeling. Mach-Zehnder interferometer is also set in order to test its potential use on a combined MachZehnder/Sagnac system. New applications and technology enhancement can be explored. This is a first experimental work applying this kind of fiber sensor at LabTel and serves as a reference for future developments.